HL-TRP channel is required for various repellents for the parthenogenetic Haemaphysalis longicornis - Ceyan Kuang; Jie Cao; Yongzhi Zhou; Houshuang Zhang; Yanan Wang; Jinlin Zhou (Parasites & Vectors)
Abstract Background Ticks can transmit a wide range of pathogens that endanger human and animal health. Although repellents are commonly used for tick control, understanding their mechanisms aren't  complete. Methods The repellent effects of N, N-diethyl-meta-toluamide (DEET); sec-butyl 2-(2-hydroxyethyl) piperidine-1-carboxylate (icaridin); N, N-diethyl-3-methylbenzamide (IR3535); and cinnamaldehyde on the parthenogenetic tick Haemaphysalis longicornis at the nymph stage were assessed using Y-tubes. The involvement of transient receptor potential (HL-TRP) channel molecules in the repellent mechanism was investigated through in situ hybridization, subcellular localization, real-time fluorescence quantitative polymerase chain reaction (PCR), RNA interference, and electroantennography. In addition, the binding affinity of HL-TRP molecules to repellents was predicted using AlphaFold3. Results DEET, icaridin, IR3535, and cinnamaldehyde have been shown to effectively repel nymphs. HL-TRP channel is shared among various arthropods, particularly several species of ticks. It is localized to the cell membrane and Haller’s organ. Moreover, microinjection of double-stranded RNA elicited tick repellency behavior, and the electroantennogram responses to those repellents were significantly decreased. The TYR783 site was proposed as an essential binding site to establish hydrogen bonds with icaridin, DEET, and cinnamaldehyde. Conclusions This exploration of ticks and repellents found that HL-TRP channel functions as a chemosensory receptor for repellents and, thereby, mediates avoidance behavior. Graphical Abstract